2024
DOI: 10.3390/ijms25010609
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Repurposing of Sitagliptin as a Drug Candidate for Colorectal Cancer by Targeting CD24/CTNNB1/SOX4-Centered Signaling Hub

Jing-Wen Shih,
Alexander T. H. Wu,
Ntlotlang Mokgautsi
et al.

Abstract: Despite significant advances in treatment modalities, colorectal cancer (CRC) remains a poorly understood and highly lethal malignancy worldwide. Cancer stem cells (CSCs) and the tumor microenvironment (TME) have been shown to play critical roles in initiating and promoting CRC progression, metastasis, and treatment resistance. Therefore, a better understanding of the underlying mechanisms contributing to the generation and maintenance of CSCs is crucial to developing CSC-specific therapeutics and improving th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…8 A), whilst no interaction was found with SIRT3, although recent evidence described a SIRT3-DPP4 interaction [ 49 ]. Moreover, recent evidence has shown that DPP4 promotes the development, progression and metastasis of CRC, making it a potential and novel therapeutic target for CRC [ 50 ]. To this end, to investigate the SGLT2 and SIRT3 capacity to modulate DPP4 protein levels, immunoblotting analysis with both iSGLT2 and SIRT3 silencing was performed (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 A), whilst no interaction was found with SIRT3, although recent evidence described a SIRT3-DPP4 interaction [ 49 ]. Moreover, recent evidence has shown that DPP4 promotes the development, progression and metastasis of CRC, making it a potential and novel therapeutic target for CRC [ 50 ]. To this end, to investigate the SGLT2 and SIRT3 capacity to modulate DPP4 protein levels, immunoblotting analysis with both iSGLT2 and SIRT3 silencing was performed (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Further investigations suggested DPP4 as a downstream target of SGLT2 and SIRT3, as revealed by the ability of both SGLT2 inhibition and SIRT3 silencing to modulate the peptidase protein levels in HCT 116 and HT-29 cells. Recent evidence described the crucial role of DPP4 in CRC initiation and progression and demonstrated the association of DPP4-inhibitor treatment with a better prognosis of CRC patients [ 50 , 83 ]. The correlation of SGLT2/SIRT3 with DDP4 regulation has been independently described, although in different experimental models [ 49 , 84 ].…”
Section: Discussionmentioning
confidence: 99%